Fast because it’s just: fostering acceptance to accelerate sustainability transitions in coal-dependent regions - Cristian Pons-Seres de Brauwer; Paola Andrea Yanguas Parra (Environmental Research: Energy)
Coal-dependent communities and regions are at the frontline of the global energy transition, with net-zero scenarios requiring unprecedented sharp decreases in coal use and production in the next few decades. Rapid decarbonization in these ‘coal-dependent’ regions can result in high disruptiveness and trigger socio-political resistance across both the acceleration of coal phase-outs (decline) and clean energy phase-ins (diffusion). Lack of social acceptance (SA) stands as a critical bottleneck risking slowing down the pace of the transition. Governance strategies seeking the acceleration of coal transitions will therefore need to strike a delicate balance between disruptiveness and acceptance . We argue that fostering acceptance, for instance through just transition (JT) policies, does not simply serve as a means to pursue ‘just’ transition processes, but rather as a fundamental acceleration strategy for decline and diffusion dynamics that unfold simultaneously. To substantiate this argument, we conduct a narrative review cutting across the literature on JTs and SA of renewables’ innovations, and reinterpret them using a socio-technical (sustainability) transition perspective to outline three core propositions: (i) justice perceptions underlie acceptance; (ii) acceptance precedes reorientation; (iii) reorientation as a transition acceleration strategy. We then outline an integrative research agenda to renew the scientific focus towards the interconnections between justice-acceptance-acceleration in the ongoing transitions in coal-dependent regions and elsewhere.